Vitamin K-3 family members - Part II: Single crystal X-ray structures, temperature-induced packing polymorphism, magneto-structural correlations and probable anti-oncogenic candidature - Rane, Sandhya; Ahmed, Khursheed; Salunke-Gawali, Sunita; Zaware, Santosh B.; Srinivas, D.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Journal of Molecular Structure, 2008)
Temperature-induced packing polymorphism is observed for vitamin K-3 (menadione, 3-methyl-1,4-naphthoquinone, 1). Form la crystallizes at 300 K and 1b at 277 K both in the same space group P2(1)/c. Form 1b contains one molecule per asymmetric unit, performing anisotropy in g-factor viz. g(z) = 2.0082, g(y) = 2.0055 and g(x) = 2.0025, whereas form 1a contains two molecules in its asymmetric unit. Vitamin K-3 family members 2, [2-hydroxy vitamin K-3] and 3, [2-hydroxy-1-oximino vitamin K-3] also perform intrinsic neutral active naphthosemiquinone valence tautomers even in dark having spin concentrations due to hydrogen bonding and aromatic stacking interactions which are compared to vitamin K-3. The significant lateral C-H center dot center dot center dot O and O-H center dot center dot center dot pi bifurcated or pi-pi(center dot) interactions are discussed for molecular associations and radical formations. X-ray structure of 3 revealed pi-pi(center dot) stack dimers as radicals signatured in PR as triplet with five hyperfine splits [(A) over bar(N-14) = 11.9 G]. The centrosymmetric biradicals in 3 show diamagnetism at high temperature but below 10 K it shows paramagnetism with mu(eff) as 0.19 B.M. Vitamin K-3 and its family members inhibit biological activities of acid phosphatase (APase), which are proportional to their spin concentrations. This may relate to their probable anti-oncogenic candidature in future. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Anti-oncogenic candidature; H-bonding; Magneto-structural correlations; Naphthosemiquinones in vitamin K-3 family; Packing polymorphism; Spin concentrations

Magnetic phase transition in valence tautomers as polymorphs of 3-iodolawsone: Single crystal X-ray structure, DSC and EPR studies - Zaware, Santosh B.; Dagade-Waghmode, Shobha; Gonnade, Rajesh G.; Srinivas, Darbha; Rane, Sandhya Y. (Journal of Molecular Structure, 2009)
Three polymorphs of 3-iodolawsone (I-III) have been isolated and characterized by single crystal X-ray diffraction, electron paramagnetic resonance (EPR) spectroscopy and differential scanning calorimetry (DSC) techniques. Polymorphs I and II were crystallized from methanol in two different valence tautomeric forms: hydroxynaphthoquinone (HNQ) and hydroxynaphthoseimquinone (HNSQ) as needles and thick plates, respectively. Polymorph III was crystallized from ethanol in HNQ form, as thin plates Chiral crystals of I belongs to the orthorhombic P2(1)2(1)2(1) space group: II and III belong to the monochnic non-centrosymmetric space group Cc. The molecules are packed via O-H O bonding and pi . pi stacking interactions. The study reveals that relatively stronger intermolecular H-bonding (2.02 angstrom) and most favoured pi . pi stacking (similar to 3 49 angstrom) interactions lead II to HNSQ radicals, presence of which was confirmed by EPR (g = 2.0052) spectroscopy. Interestingly, these materials exhibit crystal-to-crystal magnetic phase transition from polymorph I (diamagnetic) to polymorph II (paramagnetic structure) at 171.1 degrees C as identified by DSC and X-ray crystallographic studies (C) 2009 Elsevier B.V. All rights reserved
Keywords: 3-Iodolawsone; Hydroxynaphthoquinone (HNQ); Hydroxynaphthosemiquinone radical (HNSQ); Magnetic phase transition; Polymorphs; Valence tautomers

Antioxidant and anticancer activities of supramolecularly controlled magnetostructural halo-oximes of lawsone - Zaware, Santosh B.; Gonnade, Rajesh G.; Srinivas, Darbha; Khan, Ayesha A.; Rane, Sandhya Y. (New Journal of Chemistry, 2011)
Crystal engineering based on halogen bonding together with host-guest interactions of water molecules via H-bonding, stabilizing supramolecular architecture in chloro 1, bromo 2 and iodo 3 oximes of lawsone, is discussed. 1 and 2 crystallize in orthorhombic, non-centrosymmetric space group Pna2(1) while 3 crystallizes in monoclinic P2(1)/n space group. Non-covalent competitive interactions of asymmetric solvation and halogen bonding can have a large influence on the spin distribution in 1, 2 and 3 derivatives of spin carrier lawsone live polymer as revealed by single crystal X-ray and EPR studies. The significant C3-Cl/Br center dot center dot center dot O, C3-Cl/Br center dot center dot center dot H, O-H center dot center dot center dot O-C, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions have been identified in the molecular assemblies leading to net magnetostructures of halo-oximes. Dimer-of-dimer-type tetrameric radical assembly of 3 and interacting bi- and monoradical chain on 2(1) axis in 1 and 2 have been identified. The proton-coupled electron transfers possibly govern the antioxidant nature in halooximes of spin carrier lawsone in terms of oxygen reduction to water molecules. Such activity is found to be directly proportional to the spin (radical) concentrations in 1 to 3 and increases in order 1 < 2 < 3 according to halogen bonding effect. The antioxidant chemical DPPH assays for scavenging of such free radicals result in similar trend of increasing order like 1 < 2 < 3, but the chemical in vitro as well as ex vivo SOD antioxidant activities and biological anticancer activity on MCF-7, Hela and HL-60 cell lines show the increasing order 3 < 2 < 1 according to H-bonding effect. This probably could be attributed to the conversion of superoxide radical ions into H(2)O(2), which leads to greater oxidative stress leading to apoptosis.